From the Streets to the Chamber: Social Movements and the Mining Ban in El Salvador - Spalding, Rose J. (European Review of Latin American and Caribbean Studies, 2018)
Following an extended anti-mining campaign, El Salvador became the first country to adopt a legal ban on all forms of metallic mining. This article uses process tracing to map direct, indirect and mediated linkages between the anti-mining mobilization and the formal adoption of a mining prohibition by the national legislature in 2017. It draws on 78 interviews with campaign activists, legislators, government officials, business leaders and legal teams, and combines this information with legislative documents and reports, public opinion data, legal documents from an investment dispute filed against the Salvadoran government, and blogs and website of the Mesa Nacional Frente a la Minería Metálica. This analysis gives particular attention to the spatial reach and breadth of the anti-mining networks; fissures within and situational realignment of the political elite; and the strategic use of diverse institutional openings (docking points), some of which were adapted to new purposes by movement entrepreneurs. Although major obstacles to sustainable development and environmental protection remain in El Salvador, this article identifies a set of iterative interactions between activist alliances and institutional actors that can successfully contribute to policy change.Resumen: De las calles a la Cámara: Movimientos sociales y la prohibición de la minería en El SalvadorTras una extenso periodo minero, El Salvador se convirtió en el primer país en adoptar una prohibición legal de toda manera de minería metálica. El presente artículo emplea el rastreo de procesos para ilustrar los vínculos directos, indirectos y mediáticos entre la movilización anti-minera y la adopción formal de una prohibición minera por parte de la legislatura nacional en 2017. Se basa en 78 entrevistas a activistas de campaña, legisladores, funcionarios gubernamentales, líderes empresariales, y equipos legales, y combina esta información con documentos e informes legislativos, datos de opinión pública, documentos legales de una disputa de inversión presentada contra el gobierno salvadoreño, blogs y la página web de la Mesa Nacional Frente a la Minería Metálica. Este análisis presta especial atención al alcance espacial y a la amplitud de las redes anti-mineras; fisuras internas y realineación situacional de la élite política, y el uso estratégico de diversas aperturas institucionales (puntos de atraque), algunas de las cuales fueron adaptadas a nuevos propósitos por los empresarios del movimiento. Aunque los principales obstáculos para el desarrollo sostenible y la protección ambiental continúan en El Salvador, este artículo identifica un conjunto de interacciones iterativas entre las alianzas activistas y los actores institucionales que pueden contribuir con éxito al cambio de políticas.